ANALISIS PELAKSANAAN PRAKTIKUM MORFOLOGI TUMBUHAN MAHASISWA PENDIDIKAN BIOLOGI FKIP UMS TAHUN AJARAN 2017/2018 - Lina Agustina; Rivky Arif Rahmat (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2019)
The purpose of this research is to know the practical implementation of the morphology of the plant biology education students FKIP UMS 2017/2018 school year. This research is descriptive research with the research sample is a student semester 1 Biology education UMS, which travels the eyes of practical morphology of plants taken with Taro Yamane formula to get the number of samples in overall by as much as 81 students. Data collection techniques by using question form. The results of the analysis of the data shows that in practical plant morphology, 91% of students familiar with plants/preparations are used, 53% of the students stated the time used in practical enough to complete the practical work, and from the a series of practical work each meeting there is a 65% of students who have difficulty in observing and drawing plant organs into practical report. Key words: analysis, practical plant morphology